2018
DOI: 10.21873/anticanres.12501
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Obstruction Syndrome (Veno-occlusive Disease) Following Hematopoietic Stem Cell Transplant: Insights and Therapeutic Advances

Abstract: Hepatic sinusoidal obstruction syndrome (SOS) is a rare fatal clinical entity seen following hematopoietic stem cell transplant (HSCT). It is more commonly reported to occur following allogeneic HSCT compared to autologous HSCT. Historically, it is known as hepatitis following HSCT. It is thought that endothelial damage to the hepatic venules leading to occlusion of the terminal hepatic venules and hepatic sinusoids is the trigger for the development of SOS. Several risk factors have been associated with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“… 9 In the literature, MRI scans of HVOD showed hepatomegaly, ascites, hepatic vein narrowing, gallbladder wall thickening, periportal cuffing, or patchy signal enhancement of the liver. 10 , 11 , 12 The MRI of this patient presented similar imaging findings suggesting the possibility of HVOD. Histological evidence of HVOD remains the gold standard (but not mandatory) for the diagnosis.…”
Section: Discussionsupporting
confidence: 60%
“… 9 In the literature, MRI scans of HVOD showed hepatomegaly, ascites, hepatic vein narrowing, gallbladder wall thickening, periportal cuffing, or patchy signal enhancement of the liver. 10 , 11 , 12 The MRI of this patient presented similar imaging findings suggesting the possibility of HVOD. Histological evidence of HVOD remains the gold standard (but not mandatory) for the diagnosis.…”
Section: Discussionsupporting
confidence: 60%
“…In the West, HSOS is often observed following the high-dose chemotherapy used in hematopoietic stem cell transplantation (HSCT). Toxic metabolites arising from chemotherapy used in HSCT can lead to the injury of sinusoidal endothelial cells and hepatocytes, and the obstruction of the hepatic sinusoids and terminal hepatic veins, thus promoting the development of hepatic dysfunction and acute portal hypertension [ 16 , 17 ]. Previous studies have shown that a history of prior liver disease and hematologic disorders are high risk factors for HSOS progression [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported the use of unfractionated or low-molecular-weight heparin for the treatment of Tusanqi-induced HSOS with success rates of 70% to 88.9%. [4][5][6][7] Anticoagulant therapy is associated with serious complications such as bleeding, which renders its use controversial. Therefore, here we retrospectively analyzed the clinical characteristics of 49 patients with Tusanqi-induced HSOS as well as the benefits and risks associated with anticoagulant therapy.…”
Section: Introductionmentioning
confidence: 99%